Alternative Punishment In The Criminal Justice System - Murshal Senjaya; Wilman Supondho Akbar (Badan Penerbit STIEPARI Press, 2024)
The urgency of alternative punishment as a substitute for imprisonment related to the purpose of punishment is driven by sharp criticism and dissatisfaction with prison sentences, especially short-term sentences, which are considered to have more negative effects (having the nature of suffering and not developing the perpetrators of criminal acts) and are no longer effective in improving the perpetrators. and tackling crime. In realizing its objectives, punishment must uphold a person's honor and dignity, punishment must also be able to make people fully aware of the actions they have committed and cause them to have a positive and constructive mental attitude towards efforts to overcome crime and the punishment is felt to be fair both to the convict and to victims or by society. Purpose theory (utilitarian) is the basis for the purpose of punishment, namely that punishment is not to decide the absolute demands of justice. So in essence there are two main aspects in the purpose of punishment which are legal interests that are to be protected in a balanced manner, namely the interests of society and the interests of the individual (perpetrator of the crime). As well as using punishment in accordance with the modern school of punishment, this school requires individualization of punishment to carry out rehabilitation and resocialization of individuals and perpetrators of criminal acts. Social work penalties can be imposed by a judge in order to minimize overcrowding in correctional institutions by implementing Article 20 of the Criminal Code or through sociological teleological interpretation of the law by harmonizing with existing regulations and not conflicting with applicable legal rules through procedures for investigating correctional institutions that experience excessive capacity. first to be submitted to the Minister of Law and Human Rights